2010
DOI: 10.1248/jhs.56.99
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Effects of Capsaicinoids on the Distribution of White Blood Cells in Rats

Abstract: The subacute effects of dihydrocapsaincin (DHC) and capsaicin (CAP) (dose = 3 mg/kg body weight per day for 10 days, subcutaueous) on the number and distribution of white blood cells (WBCs) were studied in male adult rats. The administration of DHC and CAP for 10 days decreased significantly the number of total WBCs, lymphocytes and monocyte, and increased significantly the number of the neutrophil and eosinophil without changing the number of basophil. The administration of DHC significantly decreased thymus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…1B). 5,[23][24][25][26] Statistical Analyses --Experimental data were presented as mean ± SEM. The effects of dexamethasone on the number of WBCs were evaluated by a two-way analysis of variance (ANOVA) for repeated measures.…”
Section: Fig 1 Experimental Protocol Used In the Present Studymentioning
confidence: 99%
“…1B). 5,[23][24][25][26] Statistical Analyses --Experimental data were presented as mean ± SEM. The effects of dexamethasone on the number of WBCs were evaluated by a two-way analysis of variance (ANOVA) for repeated measures.…”
Section: Fig 1 Experimental Protocol Used In the Present Studymentioning
confidence: 99%
“…24,25) In the control group, an equivalent volume of AITC-free solution was administered in the same manners. 11,13,21,23) Count Analyses of Lymphocytes --According to our recent results, 11) diurnal rhythm of the number of lymphocytes in male adult rats was observed and the lowering actions of the pungent principles of hot pappers such as capsaicin and dihydrocapsaicin on the number of lymphocytes, T-lymphocyte and B-lymphocyte were observed at 3 hr after the administration. In the present study, therefore, we analyzed the number of lymphocytes at 1-4 hr after the administration of AITC.…”
Section: Methodsmentioning
confidence: 83%
“…These findings coincide with our previous results of dihydrocapsaicin-decreased numbers of lymphocytes, T-lymphocyte and B-lymphocyte. 11,12,21) We have also reported that dihydrocapsaicin decreased the number of acquired immunity cells such as lymphocytes, T-lymphocyte and B-lymphocyte without changing the number of NK cells. 11,21) These findings suggest that immunosuppressions may be induced by pungent components such as AITC and dihydrocapsaicin.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations